Legal Protection of Women's Workers' Rights in Garment Companies in Majalengka Regency - Sapitri, Ike; Widianingsih, Ajeng; Sofia, Dinta Sayidina; Gunawan, Moh Sigit; Maulida, Irma (Journal of Legal and Cultural Analytics, 2025)
This study discusses various problems faced by women workers, including employment agreements, shuttle transportation facilities, the right to menstrual leave, and aspects of Occupational Safety and Health (K3). The purpose of this study is to identify how the policies regarding employment that apply in Majalengka Regency are mainly to ensure the fulfillment of the rights of women workers and the obstacles faced by women workers in Majalengka Regency in obtaining Legal Protection. The type of research applied by the researcher is empirical juridical research. According to Abdul Kadir Muhamad, empirical juridical research is carried out by examining secondary data first, which is then followed by collecting primary data through field studies. The results of the analysis of the protection of women workers in Majalengka Regency are in accordance with Law No. 13 of 2003 concerning Manpower has been implemented, but there are still rights that have not been fulfilled. The protection of women workers in Majalengka Regency faces several obstacles, the local government through the DISNAKER (Manpower, Cooperatives, and SMEs Office) Majalengka Regency has not fully implemented regulations on the rights of women workers. Ideally, a number of local regulations. 9 of 2022 concerning Manpower contains provisions regarding the rights of women workers, as stipulated in higher laws and regulations, namely the Manpower Law No. 13 of 2003 concerning Manpower. However, in reality, there are still many female workers who do not know the rights they should get.